The importance of mathematics and statistics support in English universities: an analysis of institutionally-written regulatory documents. Issue 3 (4th May 2022) - Croft, Tony; Grove, Michael; Lawson, Duncan
ABSTRACT: Increasing focus worldwide on accountability and quality assurance in universities has forced senior management to develop policies to address academic support at institutional-level. One such area is the mathematical and statistical skills that students in many disciplines need to succeed. In common with many countries, large numbers of students at English universities arrive inadequately prepared for their courses' quantitative demands. University-wide mathematics and statistics support provision has been developed to mitigate this problem. We explore such provision from the perspective of institutional accountability and quality assurance, researching the extent to which such support is referenced in institutionally-written regulatory documents. The documents reveal that mathematics and statistics support is stated as contributing to retention, achievement, employability and widening participation. The paper closes with implications and recommendations drawn from the analysis of these documents and therefore is of relevance to those responsible for development and implementation of institutional teaching and learning strategies.